BENCHMARK ON THE TEACHING EFFECTIVENESS OF BASIC ELECTRICITY TEACHERS IN SOUTH EASTERN NIGERIA - James E. Ogbu (European Scientific Journal, ESJ, 2012)
This study established a benchmark on the teaching effectiveness of Basic Electricity Teachers in the South Eastern states of Nigeria through effective classroom interaction analysis techniques. Four research questions and four research hypotheses guided the study. Pre-test, post-test, control group, quasi-experimental design was adopted for the study. Samples of 12 teachers and 511 SSII Basic Electricity students were randomly drawn from the population of 57 Basic Electricity Teachers and 932 students. Three validated instruments were used for data collection as follows: Basic Electricity interaction categories (BIC), Basic Electricity Interest Scales (BEIS) and Basic Electricity Achievement Test (BEAT). They were structured to cover the critical indices and criteria for wholesome teacher effectiveness. The reliability coefficient of the instruments were 0.978, 0.60 and 0.977 respectively. Percentages, mean and standard deviation were used to answer the research questions while t-test statistic and analysis of covariance (ANCOVA) were used to test the hypotheses at 0.05 level of significance. The findings of the study revealed the mean of means of critical teacher effectiveness indices and hence Basic Electricity Teachers’ effectiveness Benchmark was 58.75 score. It was then recommended that the federal and state ministries of education and Teacher Registration council should adopt this benchmark and enforce it for Basic Electricity Teachers recruitment, promotion and other academic/professional awards/rewards. After the efficacy had been established, this benchmark can then be adopted nationally for all teacher effectiveness assessments at all levels of education in Nigeria.